The Pudding of Trust - Staab, S.; Bhargava, B.; Leszek, L.; Rosenthal, A.; Winslett, M.; Sloman, M.; Dillon, Tharam S.; Chang, Elizabeth; Hussain, Farookh; Nejdl, W.; Olmedilla, D.; Kashyap, V. (IEEE, 2004)
Trust - "reliance on the integrity, ability, or character of a person or thing" - is pervasive in social systems. We constantly apply it in interactions between people, organizations, animals, and even artifacts. We use it instinctively and implicitly in closed and static systems, or consciously and explicitly in open or dynamic systems. An epitome for the former case is a small village, where everybody knows everybody, and the villagers instinctively use their knowledge or stereotypes to trust or distrust their neighbors. A big city exemplifies the latter case, where people use explicit rules of behavior in diverse trust relationships. We already use trust in computing systems extensively, although usually subconsciously. The challenge for exploiting trust in computing lies in extending the use of trust-based solutions, first to artificial entities such as software agents or subsystems, then to human users' subconscious choices.